Charlie Parker: The Nameless Ones - Book 19 - Connolly, John, 1968- (Thorndike, Maine : Center Point Large Print, 2021)
"In Amsterdam, four bodies, violently butchered, are discovered in a canal house, the remains of friends and confidantes of the assassin known only as Louis. The men responsible for the murders are Serbian war criminals. They believe they can escape retribution by retreating to their homeland. They are wrong. For Louis has come to Europe to hunt them down: five killers to be found and punished before they can vanish into thin air. There is just one problem. The sixth"--
Keywords: Parker, Charlie "Bird" -- (Fictitious character) -- Fiction; Assassins -- Fiction; Murder -- Fiction; War criminals -- Fiction; Private investigators -- Fiction; Amsterdam (Netherlands) -- Fiction; Thrillers (Fiction); Detective and mystery fiction